Who Cares (For Whom)? - Spangenberg, Joachim H.; Lorek, Sylvia (Frontiers in Sustainability, 2022)
The debate about care has intensified in the COVID-19 crisis. A consensus appears to be emerging that care work—mostly provided by women—is not only essential to our societies, but also undervalued, reputationally as well as—for the paid work—regarding its remuneration. As care is essential for the cohesion of societies, there is an urgent need to improve the situation. However, care comes in too many forms for general recommendations for improving the situation to be effective. Its majority in terms of working hours is unpaid, but the paid part of it in health, caring or education, is indispensable for any society built upon a division of labor. Finally, not every activity is work, and not every work is care—thus leisure activities are not necessarily care work. Care can be motivated by a plethora of reasons, and take a diversity of forms. To allow for effective suggestions for improvement to be formulated, we deem it necessary to more systematically distinguish different classes of care (each class of course being an ideal type including a wide range of activities). We suggest doing so by first using the “potential third party” criterion to distinguish work and non-work activities, secondly classify work according to the beneficiaries (which is closely linked to but not the same as organizational characteristics), and thirdly characterize the specific role of care work in these categories. The beneficiaries also reflect the motivation held by agents why care work is undertaken, although rarely any motivation comes in isolation. Starting from the proximate causes, the first class of care is caring for oneself, be it in terms of health care, hygiene, or the self-production of consumer goods, both short and long lived. The second class we suggest is caring for the family (native and chosen family including friends). It again includes caring for their health, but also their household (either the common one, or the one the caretaker is managing for the care receiver). It often includes nursing the elderly, disabled or young children, but can also be a kind of neighborhood support, from joint gardening to mutual help in building or renovating a flat or house. Extending the reach of care even wider, we come to care for the public good, with the community from village or city district to higher levels being the beneficiaries. This includes the volunteers working with environment, development, feminist, trade unions, food banks or belief organizations. Finally, there is a whole range of professional care activities, with the possibility to take over any of the previously mentioned activities if there is a financial benefit to be expected, or one is offered by (government) subsidies. We observe a permanent process of substituting professional, exchange value oriented care work for voluntary, use value based care, and vice versa. This dynamic, in combination with the ongoing changes of technology, social security systems and work organization in the remunerated work sets the framework conditions which will determine the future of care, commercial and societal. However, such trends are no destiny; they can be shaped by political interventions. Whether or not a professional or voluntary approach is preferable, depends on the assessment criteria applied which in turn represent political, ethical and cultural preferences.